Blood metal ion testing is an effectivescreening tool to identify poorly performing metal-on-metal bearingsurfaces. Issue 5 (May 2013) - Sidaginamale, R. P.; Joyce, T. J.; Lord, J. K.; Jefferson, R.; Blain, P. G.; Nargol, A. V. F.; Langton, D. J.
Abstract : Objectives: The aims of this piece of work were to: 1) record the background concentrations of blood chromium (Cr) and cobalt (Co) concentrations in a large group of subjects; 2) to compare blood/serum Cr and Co concentrations with retrieved metal-on-metal (MoM) hip resurfacings; 3) to examine the distribution of Co and Cr in the serum and whole blood of patients with MoM hip arthroplasties; and 4) to further understand the partitioning of metal ions between the serum and whole blood fractions. Methods: A total of 3042 blood samples donated to the local transfusion centre were analysed to record Co and Cr concentrations. Also, 91 hip resurfacing devices from patients who had given pre-revision blood/serum samples for metal ion analysis underwent volumetric wear assessment using a coordinate measuring machine. Linear regression analysis was carried out and receiver operating characteristic curves were constructed to assess the reliability of metal ions to identify abnormally wearing implants. The relationship between serum and whole blood concentrations of Cr and Co in 1048 patients was analysed using Bland-Altman charts. This relationship was further investigated in an in vitro study during which human blood was spiked with trivalent and hexavalent Cr, the serum then separated and the fractions analysed. Results: Only one patient in the transfusion group was found to have a blood Co > 2 µg/l. Blood/Serum Cr and Co concentrations were reliable indicators of abnormal wear. Blood Co appeared to be the most useful clinical test, with a concentration of 4.5 µg/l showing sensitivity and specificity for the detection of abnormal wear of 94% and 95%, respectively. Generated metal ions tended to fill the serum compartment preferentially in vivo and this was replicated in the in vitro study when blood was spiked with trivalent Cr and bivalent Co. Conclusions: Blood/serum metal ion concentrations are reliable indicators of abnormal wear processes. Important differences exist however between elements and the blood fraction under study. Future guidelines must take these differences into account.